A team fares well with a fair coach: Predictors of social loafing in interactive female sport teams - de Backer, M.; Boen, F.; de Cuyper, B.; Høigaard, R.; vande Broek, G. (Scandinavian Journal of Medicine & Science in Sports, 2015)
The present research aimed to develop and test a theoretical model that links players' perceived justice of the coach to a more optimal motivational climate, which in turn increases players' team identification and cohesion, and results in lower levels of social loafing in female sport teams. Belgian elite female basketball, volleyball, and football players (study 1; N = 259; Mage = 22.6) and Norwegian world-class female handball players (study 2; N = 110; Mage = 22.8) completed questionnaires assessing players' perceived justice (distributive and procedural), motivational climate, team identification, team cohesion (task and social), and social loafing (perceived and self-reported). In both studies, confirmatory and exploratory path analyses indicated that perceived justice was positively related to a mastery climate (P < 0.05) and negatively to a performance climate (P < 0.05). In turn, a mastery climate was linked to increased levels of team identification (P < 0.05) and task cohesion (P < 0.05). Consequently, players' perceived and self-reported social loafing decreased (P < 0.05). The findings of both independent studies demonstrated the impact of coaches' fairness, and consequently, the motivational climate created by the coach on the optimal functioning of female sport teams.